DEVELOPMENT STRATEGY OF ON-SITE DOMESTIC WASTEWATER INFRASTRUCTURE FOR SETTLEMENTS IN SPECIFIC-WATER/ SWAMP AREA (CASE STUDY : PALEMBANG AND BANYUASIN) - WULANDARI PUTRI (NIM: 35312008), DYAH
A large number of Indonesians live in areas affected by water stream, including rivers and estuaries. In general, communities live in those areas have problems with the sanitation systems, including domestic waste water treatment systems. The study focused in Seberang Ulu I Sub-district, Palembang City that represent communities live in river area; and Sungsang Village, Banyuasin District that represent estuary characteristic. The purpose of this research is to develop a decision-making system for the selection of domestic wastewater treatment technology that facilitates sustainability aspects in general and facilitates the specific conditions of swamp areas. This research was conducted in three main stages: the identification stage, the formulation of decision support system (DSS), and the application and evaluation of DSS. The identification stage was carried out in the study area, started with the observation of community’s settlement and sanitation conditions, then expanded with identification related to community’s sanitation infrastructure and identification of specific environmental conditions of water/ swamp settlements. The results of the identification phase, accompanied by identification of the sustainability criteria of sanitation proposed become preliminary data for the next stage. The second stage, formulation of DSS began with descriptive data processing to obtain the criteria for selecting technology. Those criteria then are put into the selection framework, developed in computer program, and used by adding study area data as the input, until got the recommendation of technology Thethird stage contains evaluation of selection process and selected on-site wastewater treatment technology that was achieved from the application of the developed. There are some specific issues related to the existing sanitation that been understood from the identification stage, ie a) communities in river area have been generally served by PDAM as a source of clean water, while communities in estuary area mostly rely on rain water as water source, b) Preference of wet toilets with dominance of squat toilet fabrication with swan neck on river settlements and holes on board / “WC cemplung” in estuary settlements, c) Almost the entire community already has a toilet compartment, d) Management level of public sanitation facilities is low and medium. Other than identification related with settlements and community, identification process also includes observation of water infrastructure issues related to the physical condition of the area. It was found that: a) Issue related with changes in water level: there was flux and reflux tidal condition per day, with one highest peak and one lowest peak in a month. The swamp estuary area has a greater tidal effect. The quality of estuarine water also has a higher potential for material corrosivity, due to salinity and high sulphate content. b) In relation to the swamp type of land, the soil type for both areas is soft clay with medium-plastic silt. According to finite element method, the soil has significant deformation. The physical condition analysis explains the problem of waste water infrastructure application in the study area. Decision Support System is designed to facilitate assessment of sustainability for wastewater system technology in general using scoring and criteria fulfillment between community and environmental requirement and capacity of wastewater technology, adapted from capacity factor criteria (stage I selection), continue with selection of suitability based on toilet system preferences and water supply condition as the support facilities in running both toilet and wastewater treatment system (stage II selection), and suitability with specific swamp condition especially with (a) the inundation and groundwater condition, and (b) soft-soil condition (stage III selection). From the application of the constructed decision support system, suggested technology for river settlements in Palembang city is Tripikon-S+anaerobic filter. It is the same with suggested technology in estuary settlements in Sungsang Village, Banyuasin District, with assumption of water source can be continuously supplied. While the water source judged as non-continuous supply, suggested technology is Tripikon-S as single system. Selected technology were not accomplished all the sustainability criteria in stage I selection. This becomes an input and the requirement of further evaluation for wastewater policy and facilities improvement required for settlement in specific water/ swamp area.